Design and Programming of 5 Axis Manipulator Robot with GrblGru Open Source Software on Preparing Vocational Students’ Robotic Skills - Marsono Marsono; Yoto Yoto; Agus Suyetno; Riana Nurmalasari (Journal of Robotics and Control (JRC), 2021)
The rapid development of technology at the end of this decade, the industrial world is changing the human resources they have using the help of robot technology. The use of a robot was chosen because of the accuracy and precision that it can do in doing the job. In addition, robotic technology requires only one programming to do many things. Thus, there are many advantages for companies by using robotic technology in their production processes. This research aims to designing and building arm robot prototype to teach the robotics programming language. The result of this research is an arm robot prototype with Arduino Mega 2560 based programming. In addition, the robot movement programming uses the open source GrblGru software Grbl based. The GrblGru used for interpreting G-code and to convert pulse and direction information to control the stepper motor. This research concludes that there are 5 importance steps on develop the arm robot prototype, 1. Analyze; 2. Design; 3. Develop; 4. Evaluate; and 5. Implementation. With the GrblGru software the movements of arm robot prototype can work on simulation mode and control mode, there for students easier to study robotics programming language.